THE USE OF THE EXRADIN W1 PLASTIC SCINTILLATOR FOR MEASUREMENTS IN EXTERNAL RADIOTHERAPY - Koniarová, Irena; Konček, Ondřej (Radiation protection dosimetry, 2019)
The Exradin W1 plastic scintillator (Standard Imaging) was examined for measurement suitability in high-energy photon beams, high-energy electron beams and tomotherapy in terms of dose to water for reference fields. For photon beams, pulse repetition rate dependence, calibration stability, noise from the photodiode enclosure, detector motion during treatment, output factors, off-axis doses and percentage depth doses were tested. For electron and tomotherapy beams, energy non-dependence was verified. All features make the detector suitable in small and non-standards fields, and for electron beams.
Keywords: scintilace - počítání; plastické hmoty; monitorování radiace; Radiation Monitoring; Plastics; lidé; radioterapie; Humans; Radiotherapy; Scintillation Counting